2018
DOI: 10.3390/s18124361
|View full text |Cite
|
Sign up to set email alerts
|

Indicator Layers Based on Ethylene-Vinyl Acetate Copolymer (EVA) and Dicyanovinyl Azobenzene Dyes for Fast and Selective Evaluation of Vaporous Biogenic Amines

Abstract: The article presents naked-eye methods for fast, sensitive, and selective detection of isopentylamine and cadaverine vapours based on 4-N,N-dioctylamino-4′-dicyanovinylazobenzene (CR-528) and 4-N,N-dioctylamino-2′-nitro-4′-dicyanovinylazobenzene (CR-555) dyes immobilized in ethylene-vinyl acetate copolymer (EVA). The reaction of CR-528/EVA and CR-555/EVA indicator layers with isopentylamine vapours caused a vivid colour change from pink/purple to yellow/orange-yellow. Additionally, CR-555/EVA showed colour cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This is in agreement with an imine structure in which the push-pull character is preserved but a weaker electron-acceptor group is present. A simple nucleophilic reaction at the Cβ position, as assumed by Finšgar et al for similar dicyanovinyl azobenzene dyes [26] or as is observed with thiols [25] and the cyanide anion, [35,42] would lead to a drastic upfield shift of the proton originally at the β-position as well as those of the closest thiophene ring due to a disruption of the π-conjugation from the donor to the acceptor end. The imine structure was further confirmed by mass spectrometry and the independent synthesis of PTT-imine from aldehyde 1 and n-propylamine (Scheme 1), whose 1 H and 13 At the same time, an intense emission appeared at 535 nm that steadily increased while adding amine.…”
Section: Sensing Properties In Solutionmentioning
confidence: 78%
See 2 more Smart Citations
“…This is in agreement with an imine structure in which the push-pull character is preserved but a weaker electron-acceptor group is present. A simple nucleophilic reaction at the Cβ position, as assumed by Finšgar et al for similar dicyanovinyl azobenzene dyes [26] or as is observed with thiols [25] and the cyanide anion, [35,42] would lead to a drastic upfield shift of the proton originally at the β-position as well as those of the closest thiophene ring due to a disruption of the π-conjugation from the donor to the acceptor end. The imine structure was further confirmed by mass spectrometry and the independent synthesis of PTT-imine from aldehyde 1 and n-propylamine (Scheme 1), whose 1 H and 13 At the same time, an intense emission appeared at 535 nm that steadily increased while adding amine.…”
Section: Sensing Properties In Solutionmentioning
confidence: 78%
“…Mohr et al also described a colorimetric read-out sensor based on push-pull azo dye and therefore working at wavelengths compatible with low-cost light sources and detectors. [25,26] However in all these works, the end product was not characterized or simply postulated as being the 1,2 adduct. [26] Sathiyanarayanan et al reported the design of a ratiometric PL sensor for primary amine based on a dicyanovinyl substituted phenanthridine derivatives and they clearly identified the end product as being the corresponding imine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ethylene–vinyl acetate copolymers (EVAs), polar vinyl acetate units are randomly dispersed in the backbone. These non-biodegradable polymers are used in a variety of commercial applications, such as stent coatings, intravitreal implants, contraceptive implants, and intravaginal contraceptive rings [ 134 ]. SurModics Bravo™ (a blend of poly-butyl methacrylate and polyethylene vinyl acetate polymers) is a product used as a coating for stainless steel Cypher™ stents (Cordis, Santa Clara, CA, USA) that releases the immunosuppressant rapamycin [ 135 ].…”
Section: Coating Materials Selectionmentioning
confidence: 99%
“…Frequently, chromogenic and fluorogenic dyes, such as acid-base indicators [14][15][16] porphyrins [17], phthalocyanines [18], chameleon dyes [19,20], coumarin derivatives [21], azo dyes [22,23], or nanomaterials are applied for optical BA determination. Cellulose-based microparticles bonded with a pH-indicator and a blue reference dye yielded in slow traffic light-responding (1.5 h) colorimetric sensors [16].…”
Section: Introductionmentioning
confidence: 99%